Selective sulfonylation and isonitrilation of para-quinone methides employing TosMIC as a source of sulfonyl group or isonitrile group - Qu, Chuanhua; Huang, Run; Li, Yong; Liu, Tong; Chen, Yuan; Song, Guiting (Beilstein Journal of Organic Chemistry, 2021)
Chemoselective sulfonylation and isonitrilation reactions for the divergent synthesis of valuable diarylmethyl sulfones and isonitrile diarylmethanes starting from easy-to-synthesize para-quinone methides (p-QMs) and commercially abundant p-toluenesulfonylmethyl isocyanide (TosMIC) by using respectively zinc iodide and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as catalysts were developed. The distinguishing feature of this method is that TosMIC plays a dual role from the same substrates in the reaction: as a sulfonyl source or as an isonitrile source. The synthetic utility of this protocol was also demonstrated in the synthesis of difluoroalkylated diarylmethane 5 and diarylmethane ketone derivatives 6 and 7, which are important core structures in natural products and medicines.
Keywords: chemoselective reactions; diarylmethyl sulfones; dual role; isonitrile diarylmethane; synthetic utility